The Nuclear Structure of ¹⁵¹Sm - Nelson, Erle Dewart (My University, 1972)
An experimental study of the low-lying levels of the nucleus ¹⁵¹sm has been made using the single particle transfer reactions 1) ¹⁵²Sm (d,t)¹⁵¹Sm , 2)¹⁵¹Sm(³He,α)¹⁵¹Sm, 3) ¹⁵⁰Sm (d,p)¹⁵¹Sm , 4) ¹⁵¹Sm (d,p)¹⁵²Sm, 5) ¹⁵¹Sm(d,t)¹⁵⁰Sm and 6) ¹⁵¹Sm(³He,α) ¹⁵⁰Sm. Also,inelastic scattering and Coulomb excitation experiments were performed on targets of ¹⁵¹Sm. The information obtained from these experiments when combined with the results of previous studies of the decay of ¹⁵¹Pm, has allowed definite spin and parity assignments to be made for about 15 levels in ¹⁵¹Sm, and has put limitations on the possible assignments for several others. The level scheme obtained is compared with the predictions of the Nilsson model, including the effects of Coriolis and ΔN=2 mixing.
Keywords: Physics; Physics